Мусорелла - великая и ужасная: [повесть] / Э. Н. Веркин - Веркин Эдуард (Страшилки, 2005)
Экземпляры: ф.12 (ретро) / Инвентарный номер: 41010 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 32 / ББК: 84(2Рос=Рус)6